Inclusive educational process at the university: Theoretical and experimental model of teachers' psychological readiness - V. Z. Kantor; Yu. L. Proekt (Образование и наука)
Introduction. The institutionalisation of inclusion in higher education determines new requirements for university teachers, what is also found in the field of psychological readiness for the implementation of the educational process with the participation of students with disabilities. Aim. The present research was aimed to develop theoretical framework and experimental verification of the model of psychological readiness of academic teaching staff for the implementation of an inclusive educational process. Methodology and research methods. Methodologically, the research was based on the idea that the true implementation of inclusive higher education is conditioned by the formation of an inclusive culture of university teachers, which serves as the foundation for the implementation of inclusive practices and policies and one of the immanent attributes of which is psychological readiness to implement the educational process with the participation of disabled students. In the diagnostic and methodological terms, the current study relied on the authors' questionnaire containing the blocks of questions built using a 5-point Likert scale and characterising the severity of the various components of such readiness among university teachers in relation to working with disabled students of diverse nosological groups. The survey results were analysed qualitatively and quantitatively using the Cronbach Alpha coefficient, Shapiro-Wilk, Kolmogorov-Smirnov, Mann-Whitney tests, and the median test applying the Pearson test. To check the consistency of the proposed theoretical model of the psychological readiness of university teachers to implement an inclusive educational process, structural equation modelling (or SEM - the method of asymptotically non-parametric assessment) was employed. For statistical calculations, the program IBM SPSS Statistics ver.23 and the AMOS module were used. Results. The integrative model of the psychological readiness of faculty for the implementation of an inclusive educational process has been theoretically substantiated and experimentally confirmed. This model includes a motivational-value component (the acceptance of the values of an inclusive culture, beliefs and attitudes of the teacher regarding inclusive education), an affective component (the emotional acceptance of the situation of inclusive education and its subjects) and an operational component (the teacher's assessment of own skills in using the tools of inclusive education). In the presented model, the teacher's methodical preparedness for teaching students with disabilities acts as a cognitive component, and the resulting component is the implementation of inclusive practice based on the willingness and ability to interact with students with disabilities. It was found that, to the greatest extent, university teachers have formed a motivational readiness to implement inclusive education, but they experience a deficit of operational skills, when working with students with disabilities. At the same time, the level of psychological readiness to implement an inclusive educational process significantly differs depending on the subject specialisation of teachers and the presence / absence of previous experience of interaction with people with disabilities. Scientific novelty. The model of the psychological readiness of teachers for the implementation of inclusive education in Russia was developed and empirically confirmed. Practical significance. The findings of this research highlight the significance of the stages of the formation of university teachers' psychological readiness for inclusive education. The following stages are determined: from providing basic methodological readiness in the framework of professional development through the creation of internal conditions for readiness for inclusive education, examining the experiences and psychological difficulties in interacting with people with disabilities, and, finally, to accompanying the actual inclusive teaching practice.